2019
DOI: 10.1259/dmfr.20170450
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of diagnosis of early stage interproximal caries with bitewing radiographs and periapical images using consensus reference

Abstract: BTWs offer a significant advantage over PAs in the diagnoses of early stages of interproximal carious lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
0
12
0
5
Order By: Relevance
“…6 BW is also superior to pa in caries detection. 7 Results from this study show that most dentists know and practice caries detection using BW. A minority might make a mistake of relying on less than optimum diagnostic tools and the reason for this is either "time" or lack of knowledge, neither of which is acceptable if a diagnostic error is made.…”
Section: Discussionmentioning
confidence: 76%
“…6 BW is also superior to pa in caries detection. 7 Results from this study show that most dentists know and practice caries detection using BW. A minority might make a mistake of relying on less than optimum diagnostic tools and the reason for this is either "time" or lack of knowledge, neither of which is acceptable if a diagnostic error is made.…”
Section: Discussionmentioning
confidence: 76%
“…The research performed by Takahashi., et al [47] to assess the diagnostic property of intraoral bitewing radiographs (BTW) compared with periapical radiographs (PA) showed that there was no significant difference in the specificity of BTW and PAs; moreover, they founded that BTWs offer a significant advantage over PAs in the diagnoses of early stages of interproximal carious lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Higher sensitivity is required for early detection of dental caries, such as in enamel. BWR show significantly better sensitivity than periapical radiographs for all levels of caries progression (BWR: 94.5 for dentin caries, 90.43-82.7 for enamel caries, periapical: 69.7 for dentin caries, 39.01-56.2 for enamel caries), although there was no significant difference on specificity (18).…”
Section: Introductionmentioning
confidence: 87%
“…MID is a viable treatment option for enamel caries, in that false positives (caries misdiagnosed as being present when it is actually not) would not lead to treatments that irreversibly cause tooth structure to be removed from a healthy tooth (18). Previous studies have shown that BWR offer a significant advantage over periapical radiographs in the diagnosis of early stages of interproximal caries (IC) (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation